Novel CNNM2 Mutation Responsible for Autosomal-Dominant Hypomagnesemia With Seizure - Tseng, Min-Hua; Yang, Sung-Sen; Sung, Chih-Chien; Ding, Jhao-Jhuang; Hsu, Yu-Juei; Chu, Shih-Ming; Lin, Shih-Hua (Frontiers in Genetics, 2022)
CNNM2 is primarily expressed in the brain and distal convoluted tubule (DCT) of the kidney. Mutations in CNNM2 have been reported to cause hypomagnesemia, seizure, and intellectual disability (HSMR) syndrome. However, the clinical and functional effect of CNNM2 mutations remains incompletely understood. We report our clinical encounter with a 1-year-old infant with HSMR features. Mutation screening for this trio family was performed using next-generation sequencing (NGS)-based whole-exome sequencing (WES) with the identified mutation verified by Sanger sequencing. We identified a de novo heterozygous mutation c.G1439T (R480L) in the essential cystathionine β–synthase (CBS) domain of CNNM2 encoding CNNM2 (cyclin M2) without any other gene mutations related to hypomagnesemia. The amino acid involved in this missense mutation was conserved in different species. It was also found to be pathogenic based on the different software prediction models and ACGME criteria. In vitro studies revealed a higher expression of the CNNM2-R480L mutant protein than the wild-type CNNM2. Like the CNNM2-wild type, the proper localization of CNNM2-R480L was shown on immunocytochemistry images. Mg2+ efflux assay in murine DCT (mDCT) cells revealed a significant increase in intracellular Mg2+ Green in CNNM2-R480L compared to CNNM2-WT. By use of a simulation model, we illustrate that the R480L mutation impaired the interaction between CNNM2 and ATP-Mg2+. We propose that this novel R480L mutation in the CNNM2 gene led to impaired binding between Mg2+-ATP and CNNM2 and diminished Mg2+ efflux, manifesting clinically as refractory hypomagnesemia.